Functional Magnetic Resonance Imaging in Narcolepsy and the Kleine–Levin Syndrome - Engström, Maria; Hallböök, Tove; Szakacs, Attila; Karlsson, Thomas; Landtblom, Anne-Marie (Frontiers in Neurology, 2014)
This work aims at reviewing the present state of the art when it comes to understanding the pathophysiology of narcolepsy and the Kleine-Levin syndrome from a neuroimaging point of view. This work also aims at discussing future perspectives of functional neuroimaging in these sleep disorders. We focus on functional magnetic resonance imaging (fMRI), which is a technique for in vivo measurements of brain activation in neuronal circuitries under healthy and pathological conditions. fMRI has significantly increased the knowledge on the affected neuronal circuitries in narcolepsy and the Kleine-Levin syndrome. It has been shown that narcolepsy is accompanied with disturbances of the emotional and the closely related reward systems. In the Kleine Levin syndrome, fMRI has identified hyperactivation of the thalamus as a potential biomarker that could be used in the diagnostic procedure. The fMRI findings in both narcolepsy and the Kleine-Levin syndrome are in line with previous structural and functional imaging studies. We conclude that fMRI in combination with multimodal imaging can reveal important details about the pathophysiology in narcolepsy and the Kleine-Levin syndrome. In the future, fMRI possibly gives opportunities for diagnostic support and prediction of treatment response in individual patients.